Penerapan Metode Index Card Match untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam Kelas VIII di SMP IT Baitul Muslim - Nasehah, Itmamul Fadilatun (Universitas Muhammadiyah Tangerang, 2024)
ABSTRACT This study aims to improve students' interest in learning by applying the Index Card Match method in Islamic Religious Education in class VIII of SMP IT Baitul Muslim, Way Jepara District, East Lampung Regency. The main problem faced is the low interest in learning students in Islamic Religious Education, which affects their involvement and understanding of the material being taught. The method used in this study is Classroom Action Research (CAR) with an observation and interview approach carried out through several cycles, namely pre-cycle, cycle I, and cycle II. The subjects of this study were 22 female students of class VIII Dewi Sartika. The study results showed a significant increase in students' interest in learning, namely from 58.03% in the pre-cycle, increasing to 76.93% in cycle I, and reaching 91.02% in cycle II. The application of the Index Card Match method has proven effective in creating an interactive and collaborative learning atmosphere, which ultimately succeeded in increasing students' interest in learning. The findings of this study are expected to provide practical contributions in the application of fun and relevant active learning strategies in the field of Islamic Religious Education, as well as broaden references for educators in choosing attractive and appropriate approaches to learning.Keywords: Index Card Match, Learning Interest, Islamic Education